Механизмы сезонной цикличности размножения птиц. Сообщение V. Механизмы действия света на функцию размножения птиц - Новиков, Б.Г. (Вестник зоологии, 1977)
Data from literature and results of the author's investigations concerning mechanisms of light effect on the reproduction function in birds are generalized in the article. Light receptors and conductors as well as peculiarities of the photoperiodic reaction of the hypothalamo-hypophysial system are considered.